A study on how ergonomics and working environment can improve job satisfaction at FELDA Holdings Berhad/ Jeffrey Awang - Awang, Jeffrey (Faculty of Business and Management, 2010)
This study is about to investigate how ergonomics and working environment do can improve job satisfaction among employees at FELDA Holdings Berhad at Kuala Lumpur. There are several objectives of the study, first is to investigate the level of job satisfaction among employees at FELDA Holdings Berhad, Kuala Lumpur. Second is to identify the relationship between independent variables and dependent variable. Third is, to suggest some possible recommendations and suggestions to improve level of employee’s job satisfaction at FELDA Holdings Berhad. This study concentrates on three variables of employee’s job satisfaction at FELDA Holdings Berhad, Kuala Lumpur. The dependent variable is level of employee’s job satisfaction. For the independent variable there are ergonomics and working environment. Data collected was analyzed by using the Statistical Package for Social Science (SPSS). A sample of 45 staffs in FELDA Holdings Berhad, Kuala Lumpur has completed questionnaire measures and recorded. In the chapter four will explain the finding analysis and interpretation in this study. This chapter comprises the testing reliability analysis, frequency analysis, descriptive analysis and coefficient correlation. The research provides useful information on the level of employee’s job satisfaction at FELDA Holdings Berhad, Kuala Lumpur. This study also will support a better evaluation of development policies of working environment conditions and equipment by the management.